EDUKASI KESEHATAN DAN KESELAMATAN KERJA BAGI PETANI GAMBIR DI BATANG KAPAS KABUPATEN PESISIR SELATAN - Fea Firdani; Sepri Reski; Azyyati Ridha Alfian (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Gambir is a leading commodity from West Sumatra and has been processed for generations. Gambir farmers have not received attention in occupational health and safety (K3) services. In processing gambier, there are various occupational hazards to gambier farmers; if no preventive measures are taken, it can cause health problems due to work. Limited knowledge and the absence of health and safety guidance at work have caused Gambir farmers to consider the application of Work Safety and Health culture in their daily work not to be a concern. The purpose of this activity is to increase the knowledge and understanding of gambier farmers about the importance of applying the principles of Occupational Safety and Health in the workplace so that gambier farmers can avoid occupational hazards and risks. The activities were carried out in the form of Focus Group Discussions (FGD) and counseling on work safety, personal protective equipment (PPE) to prevent hazards and risks of work accidents and occupational diseases for gambier farmers in Batang Kapas, Pesisir Selatan. The activity was effective, and the goal was achieved by increasing the insight of gambier farmers about the dangers and risks in the gambier processing process. The farmer groups who attended directly practiced personal protective equipment so that farmers' understanding of work safety was increased. It is hoped that there will be sustainable occupational health and safety development for gambier farmers and inter-sectoral collaboration.